Penerapan Artifical intelligence dalam Administrasi Pendidikan untuk Meningkatkan Transparansi dan Akuntabilitas di Yayasan Pendidikan Garuda Khatulistiwa Kubu Raya - Agersi Diah Anggraini (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to examine the application of artificial intelligence (AI) technology in educational administration to increase transparency and accountability at the Garuda Khatulistiwa Education Foundation. This research uses a qualitative approach and case study method, data collected through observation, interviews and document analysis. The research results show that the application of AI at the Garuda Khatulistiwa Education Foundation in several aspects of educational administration, including student data management, financial management and teacher performance evaluation, can improve operational efficiency and more accurate reporting mechanisms. The application of AI can speed up the decision-making process and provide easier access to relevant information for all stakeholders. These findings show that the integration of AI technology not only provides a good level of transparency in the management of educational foundations but also increases accountability for the parties involved. Therefore, the application of AI can be used as a significant innovation in efforts to improve the management of education administration at the Garuda Khatulistiwa Education Foundation